Cow and calf performance as affected by nitrogen fertilization and burning of bluestem pastures - Berger, Loren Lynn; Schalles, R.R.; Harbers, L.H.; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Burning and fertilizing treatments on six Bluestem pastures were evaluated by comparing performance of spring-calving cows and calves that grazed them. Two control pastures were not burned or fertilized, two pastures were burned, and two were burned and fertilized with 40 pounds of nitrogen an acre, applied aerially. Neither average daily gains of the calves nor reproductive performance of the cows differed significantly among treatments.
Keywords: Beef; Performance; Fertilization; Bluestem pastures